The Interplay between Stigma, Collective Efficacy, and Advocacy Communication among Men Who Have Sex with Men and Transgender Females. Issue 7 (3rd July 2018) - Thaker, Jagadish; Dutta, Mohan; Nair, Vijay; Rao, Vishnu Prasad
Abstract : Stigma and discrimination are primary drivers of health disparities among marginalized communities. Drawing on stigma management, minority stress model, and social cognitive theories, this article tests the interplay between dimensions of stigma, collective efficacy, and advocacy communication among men who have sex with men (MSM) and transgender females. Using data from a cross-sectional survey conducted in south India ( N  = 225), five distinct dimensions of stigma were identified using factor analysis: experienced stigma, self-stigma, felt normative stigma, and two new dimensions—HIV-related vicarious stigma and media stigma. Respondents reported highest levels of media stigma. While most of the dimensions of stigma were negatively associated with both collective efficacy and advocacy communication, collective efficacy mediated the relationship between stigma and advocacy. Implications for public health campaigns among MSM groups are discussed.